Hubungan Pengetahuan Sikap Uang Saku dan Kelompok Teman Sebaya Terhadap Periaku Merokok - Damayanti, Yossi Fitria; Hermawan, Aan; Dwiani, Yasintha Muharrami (JURNAL KESEHATAN TERAPAN, 2024)
Smoking has become a common thing among teenagers, which has an impact on teenagers' intelligence and learning abilities. Additionally, smoking also affects health, such as respiratory disorders, dental damage, and premature aging. This study was conducted at MAN 14 B East Jakarta with the aim of examining the relationship between knowledge, attitudes, allowance, and peer groups. The research design employed was a quantitative study with a cross-sectional approach. The primary data was collected using a questionnaire administered directly to the respondents. Out of 80 smoking students, it was found that 53.8% engaged in light smoking behavior, 22.5% engaged in moderate smoking behavior, and 23.8% engaged in heavy smoking behavior. In terms of knowledge, the highest value was found in low knowledge, with 35 students. In terms of attitudes, the highest value was found in negative attitudes, with 42 students. As for the allowance, 42 students had a high amount of allowance, and there were 44 students who were influenced negatively by peer groups. Based on the research findings, it can be concluded that there is a significant relationship between low knowledge (0.000), attitudes (0.015), allowance (0.003), and peer groups (0.000)with smoking behavior among male students in grades X and XI at MAN 14 B East Jakarta in 2023.